Sex differences in hospitalisation and healthcare utilisation for patients with atrial fibrillation Middeldorp et al. Sex differences in healthcare utilisation and AF - Melissa E. Middeldorp; Colinda van Deutekom; Liann I. Weil; Isabelle C. Van Gelder; Ursula W. De Ruijter; Patrick T. Jeurissen; Emelia J. Benjamin; Barbara C. van Munster; Michiel Rienstra (International Journal of Cardiology: Heart & Vasculature, 2025)
Background: There is limited data on sex differences in healthcare utilization among patients with atrial fibrillation (AF). This study aimed to assess the association of sex and age on healthcare utilization in AF patients. Methods: We conducted a retrospective analysis of electronic health records from three hospitals in the Netherlands, including all patients ≥ 18 years with at least one healthcare encounter (outpatient, emergency visit, or inpatient stay). AF diagnoses were identified using ICD-10 codes linked with the Dutch Hospital Data Clinical Classification Software. Results: Of 226,991 patients, 5127 (2.3 %) had AF (44 % females, mean age 68 ± 12 years). There were no sex differences in outpatient, emergency, or inpatient visits overall. However, females aged 18–59 had more outpatient visits compared to males (6.1 ± 7.9 vs 4.8 ± 5.2, p = 0.001). In contrast, females aged ≥ 75 had fewer outpatient visits (7.2 vs 8.4, p < 0.001) and inpatient days (4.8 vs 5.8, p = 0.027) compared to males. After multivariable adjustment, both sexes aged ≥ 75 had increased risks of inpatient stays (Females: OR 2.53, 95 % CI 2.30–2.78; Males: OR 1.49, 95 % CI 1.46–1.62) and emergency visits (Females: OR 2.14, 95 % CI 1.94–2.35; Males: OR 1.13, 95 % CI 1.03–1.24). Significant interactions between sex and age were found, with females having higher odds of inpatient days (OR 1.99, p < 0.001) and emergency visits (OR 1.23, p < 0.001) compared to males. Conclusion: While no overall sex differences in healthcare utilization were found, significant age-related differences were observed, with females having higher hospital utilization rates, particularly for inpatient stays and emergency visits.